The Oceanographic cruise of the USCGC Burton Island to the marginal sea-ice zone of the Chukchi Sea--MIZPAC 77 - Paquette, Robert G; Bourke, Robert H. (Monterey, California. Naval Postgraduate School, 1978)
This report presents the data and briefly describes the oceanographic results of the cruise of the USCGC BURTON ISLAND to the marginal sea-ice zone of the Chukchi Sea during the period 24 July to 6 August 1977. The distribution and intensity classification of temperature finestructure is described. Plots of temperature, salinity, density (a.), and sound speed are presented for each station. A detailed discussion of salinity spike removal and data editing routines is presented in Appendix A. N66001-76-P0-00610 N66001-78-P0-00002 supported in part by the Arctic Submarine Laboratory, Naval Oceans Systems Center, San Diego, California under Project Order Nos. 00610 and 00002 http://archive.org/details/oceanographiccru00paqu